2023
DOI: 10.5155/eurjchem.14.1.114-120.2395
|View full text |Cite
|
Sign up to set email alerts
|

Composition, antioxidant and anti-inflammatory activities of different polarity extracts of Anaphalis busua from the Himalayan terrain of Uttarakhand

Abstract: The current study describes the analysis of the phytochemical composition and biological activities of various polarity extracts of the Anaphalis busua plant that was collected at an altitude of 1654 m in the Himalayan terrain of Uttarakhand, India. The extracts were prepared by the cold percolation method, which was then subjected to GC-MS for phytochemical analysis. A total of 31 compounds were identified that constituted 94.95% of the total methanolic extract. Mome inositol (31.03%) was identified as the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…This reduction, indicating the electron-donating ability of bioactive molecules, is observed in the increment in the absorbances recorded at 700 nm (Patra et al, 2016). There have been reports where the methanolic and hexane plant extracts have shown comparable reducing power activity with the RP50 values of 10.76 ± 0.01 µg/ml and 10.04 ± 0.01 µg/ml, respectively (Bahuguna et al, 2023). In this study, the RP50 values of the plant extracts were observed in the following order: CMME (56.72 ± 0.67 µg/ml) < CMHE (113.78 ± 0.99 µg/ml).…”
Section: Reducing Power Activitymentioning
confidence: 91%
“…This reduction, indicating the electron-donating ability of bioactive molecules, is observed in the increment in the absorbances recorded at 700 nm (Patra et al, 2016). There have been reports where the methanolic and hexane plant extracts have shown comparable reducing power activity with the RP50 values of 10.76 ± 0.01 µg/ml and 10.04 ± 0.01 µg/ml, respectively (Bahuguna et al, 2023). In this study, the RP50 values of the plant extracts were observed in the following order: CMME (56.72 ± 0.67 µg/ml) < CMHE (113.78 ± 0.99 µg/ml).…”
Section: Reducing Power Activitymentioning
confidence: 91%